Relevance of formation conditions to the size, morphology and local structure of intrinsic plutonium colloids. Issue 8 (14th July 2020) - Micheau, Cyril; Virot, Matthieu; Dourdain, Sandrine; Dumas, Thomas; Menut, Denis; Solari, Pier Lorenzo; Venault, Laurent; Diat, Olivier; Moisy, Philippe; Nikitenko, Sergey I.
Abstract : Fundamental knowledge about plutonium intrinsic colloids is a key issue for the prediction of plutonium transport and release rates in the environment. Abstract : Fundamental knowledge about plutonium intrinsic colloids is a key issue for the prediction of plutonium transport and release rates in the environment. Recent studies demonstrated that the particle size and surface properties of intrinsic Pu colloids are strongly influenced by the preparation method. In this work, a combination of synchrotron small angle X-ray scattering (SAXS) with X-ray absorption spectroscopy (XAS) is used to characterize two kinds of stable plutonium intrinsic colloids prepared by hydrolysis of Pu(iv ) ionic species and sonolysis of PuO2 in pure water. Despite their similarities, the multi-scale structural properties of these colloidal suspensions are found to be strongly influenced by the synthesis route. The hydrolysis approach leads to spherical nanoparticles of ca. 2.0 nm, whereas sonolytic colloids show elongated structures measuring 5.7 nm of thickness and >30 nm long. This difference results from the synthesis mechanism and can be attributed to nanoparticle aggregation in the absence of capping-ions. The results obtained by both SAXS and XAS approaches converge in the description of Pu(iv ) intrinsic colloids as core–shell nanoparticles made up of a PuO2 core covered with a disordered Pu–O shell characterized by a splitting of Pu–O and Pu–Pu distances and an associated strong increase of associated DWF parameters. The local distortions of both Pu–O and Pu–Pu coordination spheres observed by XAS seem to be correlated with the nanoparticle shrinking probed by SAXS rather from the contribution of higher Pu oxidation states. The stabilization of the hydrolytic colloidal particles is further suggested from SAXS simulation to result from interaction with counter-ions from the medium.